Design and modelling techniques for performance improvement of synchronous reluctance machines - Korman, Oguz (2024)
The design of electric machines constitutes a complex optimization problem subject to target application and performance requirements. State-of-the-art design routines generally start with adaption of a certain geometry followed by an optimization process. An optimization process has its own challenges as it shows sensitive behaviour to objectives and constraints. When the optimization problem is an electric machine design, challenge only becomes more sophisticated. Existence of non-linearity due to magnetic materials and performance requirements which more than often contradicts, requires proper handling of the optimization process. This is particularly a problem for more complex machine topologies such as synchronous reluctance (SynRel) and internal permanent magnet (IPM) machines.